1859 Wash. Sess. Laws 107-08, An Act Relative to Crimes and Punishment, and Proceedings in Criminal Cases, ch. 2, §§ 14-15, 23. - (:unkn) unknown (General Publisher, 1859)
§ 14. If either party to a duel be killed, the survivor shall be deemed guilty of murder in the second degree. § 15. If any person shall, by previous appointment made within, fight a duel without this territory, and in so doing shall inflict a mortal wound upon any person, whereof the person so injured shall die, such person so offending shall be deemed guilty of murder in the second degree, within any county in this territory. § 23. Every person who shall accept such challenge, or who shall knowingly carry or deliver any such challenge or message, whether a duel ensue or not, and every person who shall be present at the fighting of a duel with deadly weapons, as an aid, or second, or who shall advise, encourage, or promote such duel, shall, on conviction thereof, be imprisoned in the penitentiary, not more than five years nor less than six months.
--
Keywords: DUELING